Prospective evaluation of intraarticular dextrose prolotherapy for treatment of osteoarthritis in dogs - Sherwood, Jacob Matthew (Kansas State University, 2014)
The objective of this study was to evaluate the effects of intraarticular dextrose prolotherapy on osteoarthritis of the elbow or stifle in dogs. This was a randomized, double-blind, placebo controlled prospective trial of intraarticular dextrose prolotherapy given at 0 and 6 weeks for relief of osteoarthritis. Dogs with unilateral lameness were evaluated by orthopedic exam, visual lameness score, Canine Brief Pain Inventory (CBPI), goniometry, and by kinetic gait analysis at 0, 6 and 12 weeks. Joint radiographs were scored at 0 and 12 weeks. Ten client-owned dogs with naturally occurring osteoarthritis of the elbow or stifle were enrolled. Initial visual lameness, age, body weight, duration of lameness, and CBPI scores did not differ between groups. Change in CBPI PS score in the prolotherapy group from week 6-12 was significantly less improved than placebo with no other significant differences in CBPI Pain Severity (PS) or Pain Interference (PI) scores between groups. There were no significant differences for range of motion or radiographic scores between groups at any time. Kinetic forces improved in prolotherapy dogs, but were not significantly different between treatment groups at any time. There were no significant benefits of intraarticular dextrose prolotherapy for treatment of osteoarthritis of the elbow and stifle in dogs in this study. Larger enrollments and more stringent inclusion criteria should be considered in future evaluations of prolotherapy.
Keywords: prolotherapy; regenerative injection; regenerative; dextrose; intraarticular; osteoarthritis; Veterinary Medicine (0778)